2020
DOI: 10.1016/j.heliyon.2020.e04837
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia and its predictors in undergraduate students of Lahore, Pakistan

Abstract: Increasing rates of smartphone use in Pakistani undergraduate students, coupled with a dearth of research, indicate a need for a better understanding of the effects of Smartphone use on this population. This cross-sectional study therefore aimed to measure rates of nomophobia and its predictors among this understudied population. A total of 138 undergraduate students of a private university in Lahore, Pakistan completed a demographics questionnaire and the Nomophobia Questionnaire (NMP-Q) as part of a larger s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 22 publications
3
25
0
2
Order By: Relevance
“…India contributed with seven studies [2,3,[15][16][17][18][19][20], Iran [21,22], Turkey [1,23], and Pakistan [24,25] contributed each with two studies, and Australia [26], Bahrain [8], Israel [27], Italy [28], Kuwait [29], and USA [30] each contributed with one study. Fourteen studies [2,[15][16][17][19][20][21][22][23][24][25][28][29][30] (70%) of the studies recruited university students as participants, while four studies [8,18,27,28] (20%) recruited young adults and only two studies [1,3] (10%) recruited high school students. The NMP-Q was used in 12 studies [1,3,8,17,19,[24][25][26]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…India contributed with seven studies [2,3,[15][16][17][18][19][20], Iran [21,22], Turkey [1,23], and Pakistan [24,25] contributed each with two studies, and Australia [26], Bahrain [8], Israel [27], Italy [28], Kuwait [29], and USA [30] each contributed with one study. Fourteen studies [2,[15][16][17][19][20][21][22][23][24][25][28][29][30] (70%) of the studies recruited university students as participants, while four studies [8,18,27,28] (20%) recruited young adults and only two studies [1,3] (10%) recruited high school students. The NMP-Q was used in 12 studies [1,3,8,17,19,[24][25][26]…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies [2,[15][16][17][19][20][21][22][23][24][25][28][29][30] (70%) of the studies recruited university students as participants, while four studies [8,18,27,28] (20%) recruited young adults and only two studies [1,3] (10%) recruited high school students. The NMP-Q was used in 12 studies [1,3,8,17,19,[24][25][26][27][28][29][30] (60%), and the remaining used other method to assess the nomophobia, mainly researcherdeveloped research tools. Researcher studies reported the prevalence of nomophobia by severity-mild, moderate, and severe.…”
Section: Resultsmentioning
confidence: 99%
“…Moreno-Guerrero et al [ 19 ], as well as Betoncu and Ozdamli [ 14 ], Ramos-Soler et al [ 74 ], Kim, LaRose and Peng [ 75 ], and Gutiérrez-Puertas et al [ 76 ], proclaimed that the failure to communicate or reach family or friends rapidly is one of the main factors that bring the feeling of uneasiness among higher education students. The finding is significant for educational policymakers to monitor further the psychological indications of smartphone use and ownership [ 2 , 41 ], among other subpopulations in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions were coded to gain a clear understanding of the results. The NMP-Q scale provides a numerical score varying from 20 to 140, with maximum scores (NMP-Q = 140) symbolising highest severity [ 41 ] of nomophobic behaviour. A score between 100 and 140 infer severe nomophobia, scores between 60–99 indicate that nomophobia is moderate, scores 21–59 infer that nomophobia is mild, and a score of 20 infers that nomophobia is absent [ 34 , 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation